Shock in Pregnancy – Recommendations of the German Interdisciplinary Association for Intensive and Emergency Medicine (DIVI – Section Shock) and the Working Group on Obstetrics and Prenatal Medicine (AGG – Section on Maternal Disorders) - Standl, Thomas; Annecke, Thorsten; Geiger, Stefan; Kähler, Jan; Kainer, Franz; Schönenberger, Silvia; Kehl, Sven; with contributions from members of the Section Shock of the DIVI* and the AGG** (Geburtshilfe und Frauenheilkunde, 2025)
Objective The recommendations of the Shock Section of the German Interdisciplinary Association for Intensive and Emergency Medicine (DIVI) and the Maternal Disorders Section of the Working Group on Obstetrics and Prenatal Medicine (AGG) aim to improve the diagnosis and management of pregnant patients in shock. In 2018, the DIVI Shock Section published a revised classification of shock types. Given that pregnancy involves extensive physiological changes affecting all organ systems – with direct implications for the development and progression of shock – specific characteristics of shock in pregnancy were analyzed.Methods A selective literature review and iterative consensus process were conducted within the DIVI Shock Section and the Maternal Disorders Section of the AGG.Results Shock, defined as a state of circulatory failure characterized by a critical mismatch between oxygen delivery (DO2) and consumption (VO2), is common to all shock types, including in pregnant women. Unique features of pregnancy include altered sensitivity to triggering factors, modified classical shock symptoms, and specific diagnostic and therapeutic approaches to optimize outcomes for both mother and child.Conclusions The statements and recommendations facilitate the identification of underlying causes across the different forms of shock (hypovolemic, distributive, cardiogenic, and obstructive) and support the initiation of appropriate management strategies.
Keywords: pregnancy; shock; emergency medicine; obstetrics; intensive care medicine